Selective desorption of high-purity (6, 5) SWCNTs from hydrogels through surfactant modulation. Issue 14 (21st December 2015) - Zhao, Yang; Clar, Justin G.; Li, Luping; Xu, Jia; Yuan, Tianyu; Bonzongo, Jean-Claude J.; Ziegler, Kirk J.
Abstract : Selective desorption of (6, 5) single-wall carbon nanotubes from hydrogels only occurs at specific co-surfactant ratios. Abstract : Selective desorption of (6, 5) single-wall carbon nanotubes from hydrogels only occurs at specific co-surfactant ratios. High-purity fractions are obtained at this ratio even with long elution times and different total co-surfactant concentrations. These results suggest that each ( n, m ) type forms a thermodynamically-stable surfactant structure in the co-surfactant solution, enabling high-fidelity separations in a single column.